Fear of Missing Out (FOMO) in Crypto Investment Decision-Making: An Analysis of Gender Moderation Among Generation Z - Syafrina, Rifdah Dwi; Ulya, Laila Listiana (Psikoborneo: Jurnal Ilmiah Psikologi, 2026)
The increase in Generation Z participation in crypto investment in Indonesia has occurred amid high market volatility and the rise of investment trends on social media. These conditions have given rise to psychological pressures, one of which is Fear of Missing Out (FOMO). This study aims to analyze the influence of Fear of Missing Out (FOMO) on cryptocurrency investment decision-making and to examine the role of gender as a moderating variable. A quantitative approach was used with purposive sampling techniques, involving 176 Generation Z respondents who had been actively investing in cryptocurrency for at least three months. The research instruments consisted of the Cryptocurrency Fear of Missing Out (CFOMO) and Investment Decision Making (IDM) scales. Data analysis was performed using Moderated Regression Analysis (MRA). The results of the analysis showed that FOMO had a significant effect on investment decision making (p = 0.049). Gender does not directly affect investment decision making (p = 0.549), but it significantly moderates the relationship between FOMO and investment decision making (p = 0.001). The effect of FOMO was found to be stronger in men than in women. These findings confirm that gender differences affect individuals' sensitivity to psychological and social pressures in the context of cryptocurrency investment. Peningkatan partisipasi Generasi Z dalam investasi kripto di Indonesia terjadi di tengah volatilitas pasar yang tinggi serta maraknya tren investasi di media sosial. Kondisi tersebut memunculkan tekanan psikologis, salah satunya yaitu Fear of Missing Out (FOMO). Penelitian ini bertujuan untuk menganalisis pengaruh Fear of Missing Out (FOMO) terhadap pengambilan keputusan investasi kripto serta menguji peran gender sebagai variabel moderator. Pendekatan yang digunakan yaitu kuantitatif dengan teknik purposive sampling, melibatkan 176 responden Generasi Z yang aktif berinvestasi kripto minimal tiga bulan. Instrumen penelitian terdiri atas skala Cryptocurrency Fear of Missing Out (CFOMO) dan Investment Decision Making (IDM). Analisis data dilakukan menggunakan Moderated Regression Analysis (MRA). Hasil analisis menunjukkan bahwa FOMO berpengaruh signifikan terhadap pengambilan keputusan investasi (p = 0.049). Gender tidak berpengaruh langsung terhadap pengambilan keputusan investasi (p = 0.549), namun memoderasi hubungan FOMO dan pengambilan keputusan investasi secara signifikan (p = 0.001). Efek FOMO ditemukan lebih kuat pada laki-laki dibandingkan perempuan. Temuan ini menegaskan bahwa perbedaan gender memengaruhi sensitivitas individu terhadap tekanan psikologis dan sosial dalam konteks investasi kripto.